Ability Pedagogical Content Knowledge Prospective Teacher in Creating Independent Curriculum Teaching Modules - Destari, Helsa Ulfa; Hairida, Hairida; Ulfah, Maria; Junanto, Tulus; Lestari, Ira (Jurnal Pendidikan Edutama, 2024)
The presence of a teacher is one of the important factors that support the success of learning activities. Therefore, prospective teacher students need to be trained in Pedagogical Content Knowledge (PCK) skills in order to plan classroom learning effectively through the use of teaching modules. This study aimed to determine the PCK ability of chemistry education students to make teaching modules in microteaching courses. The type of research used is quantitative with descriptive methods. The research subjects were chemistry education students of class 2020 FKIP UNTAN, totaling twenty-four participants. The instruments used were teaching module assessment sheets and student PCK observation sheets. The data collection techniques used were observation and interviews. The results showed that the PCK ability of chemical education students in making teaching modules was in the good category, with an average value of content knowledge (CK) ability of 79% (good), pedagogical knowledge (PK) ability of 72% (good), and pedagogical content knowledge (PCK) ability of 78% (good). Furthermore, with the independent curriculum being implemented as a national curriculum, PCK must be prepared for the development  of independent curriculum teaching modules before teaching practice at school.